Вплив транспортування сільськогосподарської цистерни на елементи трансмісії колісного трактора в процесі розгону - Кожушко, Андрій Павлович; Трембач, Олексій Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2023)
Побудовано загальну математичну модель колісного трактора та напівпричіпної цистерни в вертикальній і горизонтальній площинах руху. Окреслена модель враховує рух підресорених та непідресорених мас транспортного засобу, а також хлюпання рідини в цистерні. Виконано аналіз зміни показника динамічної навантаженості елементів трансмісії трактора при транспортуванні сільськогосподарської напівпричіпної цистерни в процесі розгону. Як результат, отримано можливість оцінювати динамічні показники елементів трансмісії колісного трактора при виконанні транспортної роботи з перевезення рідкого вантажу

Today's technical level of agricultural wheeled tractors has the ability to be aggregated with various agricultural means for efficient performance of traction (plowing, sowing, harrowing, harvesting, etc.) and transport (transportation of solid and liquid loads) works. Among the variety of agricultural works, the greatest test of the tractor's reliability is the performance of field work on plowing the soil. But also one of the priority studies, which affects the reliability of the power plant of a wheeled tractor, is the work on the transportation of partially filled agricultural tanks. Therefore, the material of this article aims to analyze the change in the indicator of the dynamic load of the tractor transmission elements during the transportation of an agricultural semi-trailer tank during acceleration. When solving the set goal, a technique was used, which involved the formation of a general mathematical model of a wheeled tractor and a semi-trailer tank in the vertical and horizontal planes of movement. The outlined model takes into account the movement of sprung and unsprung masses of the vehicle, as well as the sloshing of liquid in the tank. As a result, it was possible to evaluate the dynamic parameters of the transmission elements of a wheeled tractor when performing transport work for the transportation of liquid cargo. The practical significance of the work lies in the possibility of its use in evaluating the dynamic performance of a wheeled tractor, which is equipped with various types of transmissions when transporting agricultural tanks.
Influence of agricultural tank transportation on transmission elements wheeled tractor during acceleration
Keywords: колісні трактори; трансмісії; цистерни; розгін; коливання; хлюпання рідини; динамічні навантаження; wheeled tractor; transmission; tank; acceleration; oscillations; liquid splash; dynamic load